PERAN INKUBASI BUDAYA TERHADAP PELESTARIAN DAN PEMAJUAN BUDAYA LOKAL ACEH - Hasbi, Hasbi; Saiful Bahgia (JURNAL KREASI RAKYAT, 2024)
Cultural advancement as an investment to build the future and civilization of the nation in order to realize the national goals as mandated by the 1945 Constitution of the Republic of Indonesia. Aceh is a region rich in local culture and is steeped in the history and civilization of the nation. This study aims to examine the development and advancement of culture through cultural incubation and analyze the role of cultural incubation in the preservation and advancement of local culture in Aceh. This study uses a descriptive qualitative approach. Data were collected through literature studies and observations of cultural advancement objects in Aceh and those stipulated in the Law of the Republic of Indonesia Number 5 of 2017. The results of the study indicate that the role of cultural incubation is very important in maintaining, developing, and advancing cultural wealth, especially in facing the challenges of globalization and digitalization. The following are the strategic roles of cultural incubation: preservation of local culture, development of a culture-based creative economy, facilitation of regeneration and transfer of knowledge, innovation and adaptation of culture, encouraging collaboration between cultural actors, strengthening identity and self-identity and advocacy of cultural policies. By strengthening various aspects of culture through collaboration, innovation, advocacy, and regeneration, we not only preserve our ancestral heritage, but also ensure that culture remains alive, relevant, and serves as a foundation for sustainable development in the future.